Magnesium sulphate as an adjuvant to bupivacaine in ultrasound-guided transversus abdominis plane block in patients scheduled for total abdominal hysterectomy under subarachnoid block - Rana, Shelly (Indian J Anaesth, 2016)
BACKGROUND AND AIMS: Transversus abdominis plane (TAP) block has proven to be an effective component of multimodal analgesic regimens for a variety of abdominal procedures. Magnesium sulphate (MgSO(4)) N-methyl-D-aspartate receptor antagonist has the potential to be an ideal adjuvant in TAP block. We studied the efficacy of MgSO(4) as an adjuvant to bupivacaine in TAP block in patients scheduled for total abdominal hysterectomy (TAH) under subarachnoid block (SAB). METHODS: Sixty-five women belonging to American Society of Anesthesiologists physical status 1 or 2, aged between 35 and 70 years, scheduled for TAH under SAB were recruited. Patients in Group B (n = 32) received 18 mL 0.25% bupivacaine (45 mg) with 2 mL normal saline (NS), whereas those in Group BM (n = 33) received 18 mL 0.25% bupivacaine (45 mg) with 1.5 mL (150 mg) MgSO(4) and 0.5 mL NS in the ultrasound (USG)-guided TAP block performed on each side after the completion of the surgery under SAB. They were evaluated for pain at 0, 2, 4, 6, 12 and 24 h, time to first rescue analgesic and duration of postoperative analgesia were noted. RESULTS: The post-operative visual analogue scale (VAS) scores were lower in Group BM at 4, 6 and 12 h (P < 0.05). Mean duration of analgesia was significantly prolonged in Group BM with lesser requirement of rescue analgesic (P < 0.05) up to 12 h. CONCLUSION: MgSO(4) (150 mg) as an adjuvant to bupivacaine in USG-guided TAP block reduces post-operative pain scores, prolongs the duration of analgesia and decreases demands for rescue analgesics.